Roundtable Do I need a new name for the Librarian? - Sequeira Ortiz, Deyanira (1998)
This roundtable is intended to stimulate discussion on a very hot topic in the library profession, leading to great competition with other professions and academic disciplines that claim jurisdiction over the informational functions that have traditionally controlled this profession. What does it take for the profession to adapt to changes in order to develop appropriate strategies?